Conditional nationally determined contributions in the Paris Agreement: foothold for equity or Achilles heel?. (20th April 2020) - Pauw, W. P.; Castro, P.; Pickering, J.; Bhasin, S.
ABSTRACT: The Paris Agreement's success depends on parties' implementation of their Nationally Determined Contributions (NDCs) towards the Paris Agreement's goals. In these climate action plans, most developing countries make their mitigation and adaptation contributions conditional upon receiving international support (finance, technology transfer and/or capacity building). While provision of support for NDC implementation could enhance equity among countries, the feasibility of NDC implementation might be challenged by the large number of conditional NDCs. This paper addresses the implications of this tension based on an analysis of all 168 NDCs. We find that feasibility is challenged because conditions applied to NDCs are often not well defined. Moreover, the costs of implementing all conditional contributions are too high to be covered by existing promises of support from developed countries, even if the entire annual 100 billion of climate finance were earmarked for NDC implementation. Consistent with principles of equity and the prioritization in the Paris Agreement, a higher proportion of Least Developed Countries (LDCs) and Small Island Developing States (SIDS) have conditional NDCs than do other countries. However, differences between the distribution of countries requesting support and those currently receiving support, in particular among middle-income countries, demonstrates potential tensions between feasibility and equity. The article concludes with recommendations on how cost estimates and updated NDCs can be strengthened to ensure support for NDC implementation is targeted more equitably and cost-effectively. Key policy insights Support requested by developing countries to implement conditional NDCs far exceeds existing funding pledges. Differences between existing patterns of financial assistance, and those implied by requests under conditional NDCs, mean that supporting NDCs may require a significant shift in provider countries' priorities for allocating climate finance. This may challenge feasibility. The Paris Agreement's provisions on prioritizing LDCs and SIDS offer valuable guidance in making difficult choices on allocating support. To increase the likelihood of attracting support, developing countries (assisted by capacity building as needed), should include credible cost estimates in future NDCs and formulate investment plans. By outlining plans to mobilize support in their NDCs, developed countries can reassure developing countries that raising the ambition of NDCs is feasible.